Physiological responses to water stress and yield of winter wheat cultivars differing in drought tolerance. (16th January 2018) - Thapa, S.; Reddy, S. K.; Fuentealba, M. P.; Xue, Q.; Rudd, J. C.; Jessup, K. E.; Devkota, R. N.; Liu, S.
Abstract: Moderate to severe drought (water stress) at the reproductive stage is common in the U.S. Southern High Plains (SHP), where wheat is grown as a major winter crop. The objective of this study was to better understand the physiological basis of drought tolerance in elite wheat cultivars. A 2‐yr glasshouse study was conducted using three cultivars (TAM 111, TAM 112 and TAM 304) and two water treatments (wet: adequate water and dry: water‐limited). Overall, TAM 111 and TAM 112 used more water for cumulative evapotranspiration (ET) and had more tillers and greater root mass and shoot mass compared to TAM 304. In the dry treatment, TAM 112 had 67% and 81% more grain yield than TAM 111 and TAM 304, respectively. Water use efficiency for grain (WUEg) and water use efficiency for biomass (WUEbm) were also greater in TAM 112 compared to the other cultivars in the dry treatment. The flag leaves in TAM 112 at mid‐grain filling stage (about 15 days after flowering) had lower stomatal conductance (Gs), intercellular CO2 concentration (Ci), transpiration rate (Tr) and net photosynthetic rate (Pn), but higher photosynthetic water use efficiency (PWUE) than TAM 111 and TAM 304 under water stress. This study demonstrated a distinct role of gas exchange parameters in response to drought, and TAM 112 was more efficient than TAM 111 and TAM 304 in evolving physiological mechanisms to adapt to water stress.